Pelaksanaan Latihan Cone Drill Exercise terhadap Peningkatan Kelincahan Atlet Bola Voli - Alvin Al Hidayath; Adi Saputra Junaidi; Putra Hadi (Prosiding Seminar Kesehatan Nasional, 2022)
Â Agility is the ability to performs movements in short time or quickly in the shortest possible time. Agility is the continuity between the combination of flexibility by the body and the continuity of the muscles that work to produce simple and complex movements, agility is a complex set of skills that a person performs to respond to external stimuli with deceleration, change of direction and reacceleration. So the characteristics of agility are the speed and accuracy of changes in running direction, changes in body position, and changes in the directions of body parts. To know the implementation of physiotherapy with cone drill exercise on the levels of agility of volleyball athletes. The results of the exercise carried out using the cone drill exercise method are there was an increase in agility in volleyball athletes with a training does of 6 times with a frequency of 3 times a week, performed in three sets and duration 20 seconds.